Estimating time‐variable aerobic respiration in the streambed by combining electrical conductivity and dissolved oxygen time series. Issue 8 (29th August 2016) - Vieweg, Michael; Kurz, Marie J.; Trauth, Nico; Fleckenstein, Jan H.; Musolff, Andreas; Schmidt, Christian
Abstract: Aerobic respiration is an important component of in‐stream metabolism. The larger part occurs in the streambed, where it is difficult to directly determine actual respiration rates. Existing methods for determining respiration are based on indirect estimates from whole‐stream metabolism or provide time invariant results estimated from oxygen consumption measurements in enclosed chambers that do not account for the influence of hydrological changes. In this study we demonstrate a simple method for determining time‐variable hyporheic respiration. We use a windowed cross‐correlation approach for deriving time‐variable travel times from the naturally changing electrical conductivity signal that is transferred into the sediment. By combining the results with continuous in situ dissolved oxygen measurements, variable oxygen consumption rate coefficients in the streambed are obtained. An empirical temperature relationship is derived and used for standardizing the respiration rate coefficients to isothermal conditions. For demonstrating the method, we compare two independent measurement spots in the streambed, which were located upstream and downstream of an in‐stream gravel bar and thus exposed strongly diverse travel times. The derived respiration rate results are in accordance with findings of other stream studies. By comparing the travel time and respiration rate coefficient (i.e., Damköhler number) we estimate the contribution of each to the oxygen consumption in the streambed. Key Points: An in situ method for estimation of streambed respiration Natural variations of EC can be used for deriving time‐variable travel times Respiration is equally influenced by temperature and hydrological dynamics